Precipitation and temperature regulate species diversity, plant coverage and aboveground biomass through opposing mechanisms in large-scale grasslands - Yao, Zhenyu; Xin, Yue; Yang, Liu; Zhao, Liqing; Ali, Arshad (Frontiers in Plant Science, 2022)
Although the relationships between species diversity and aboveground biomass (AGB) are highly debated in grassland ecosystems, it is not well understood how climatic factors influence AGB directly and indirectly via plant coverage and species diversity in large-scale grasslands. In doing so, we hypothesized that climatic factors would regulate plant coverage, species diversity and AGB due to maintaining plant metabolic and ecological processes, but the relationship of plant coverage with AGB would be stronger than species diversity due to covering physical niche space. To test this hypothesis, we collected data for calculations of species richness, evenness, plant coverage and AGB across 123 grassland sites (i.e., the mean of 3 plots in each site) dominated by Leymus chinensis in northern China. We used two separate structural equation models (SEMs) with the effects of either mean annual precipitation or temperature as well as the topographic slope on plant coverage, species richness, and evenness on AGB through direct and indirect pathways. We found that plant coverage increased AGB better than species richness but species evenness declined AGB. Precipitation increased AGB directly and indirectly via plant coverage, whereas temperature declined AGB indirectly via plant coverage but increased via species evenness. Our results showed that niche complementarity and selection effects are regulating AGB, but these processes are dependent on climatic factors. Plant coverage promoted the coexistence of species but depended greatly on precipitation and temperature. Our results highlight that precipitation and temperature are two key climatic drivers of species richness, evenness, plant coverage and AGB through complex direct and indirect pathways. Our study suggests that grasslands are sensitive to climate change, i.e., a decline in water availability and an increase in atmospheric heat.